Advances in the pathogenic classification, epidemiological monitoring and control of soybean anthracnose - LI Jianfei; WANG Xiaoxiao; SHU Yue; HUANG Qi; TANG Guixiang (浙江大学学报. 农业与生命科学版)
Anthracnose is a major disease caused by Colletotrichum Corda that significantly reduces yield and quality of soybeans. This disease is prevalent in various regions, including the main production areas of fresh soybeans in the middle and lower reaches of the Yangtze River in China, South Asia, Southeast Asia, and South America. Based on the harm, classification and incidence cycle of soybean anthracnose, we reviewed the pathogenic identification, incidence prediction in the field, green prevention and control and other related research progress, aiming to provide a theoretical basis for field surveillance and comprehensive control of soybean anthracnose.